ANALISIS TRANSPARANSI PENGELOLAAN DANA DESA DI DESA SEKARPUTIH BALONGPANGGANG GRESIK - Dewi Suprobowati; Mahfud Hariono (FISIP UWP, 2020)
This study aims to describe the transparency and weaknesses of the village government in managing village funds in the village. Sekarputih, District. Balongpanggang, Kabuaten Gresik. The method used in this study is a descriptive qualitative method and uses research data techniques with observation, interviews and documentation, and compares the results of interviews and data obtained by researchers with a theory and law. The sample used in this study is village government and community in Desa Sekarputih, Kecamatan. Balongpanggang, Kabuaten Gresik as many as 12 informants and data analysis techniques using the water model according to miles and Huberman (2012: 15-19). The results of this study indicate that the village government in Sekarputih Village is already in compliance with the reporting stage to the government by reporting through the SISKUDES system, while at the transparency stage to the community the Sekarputih village government is still less transparent. For weaknesses in realizing it is caused due to lack of community participation and understanding of the Village Fund (DD).